PENGARUH PENGGUNAAN MEDIA BONEKA TANGAN (HAND PUPPET) TERHADAP KETERAMPILAN MENYIMAK CERITA SISWA KELAS II SDN 6 MENTENG PALANGKA RAYA - Ratu Aini Aulia, Ratu Aini Aulia; Sapriline; Widya Permata Dilla (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
Based on the results of initial observations of the results of listening skills of 36 students present in class II, only 8 people or 22.22% of students in class II have reached the KKM in Indonesian language subjects, namely 76. This study aims to determine the effect of using hand puppet media on listening skills. This research is a quantitative study with the design of 'Posttest Only Control Group Design', namely there are experimental groups and control groups that are compared. This study is a population study because it examines the entire population of 46 with 23 experimental class students and 23 control class students. The results showed that t_hitung was 4.623 and t_table with a significant level of 5% (2.015). Based on these data, t_hitung (4.623) > t_table (2.015), then Ho is rejected and Ha is accepted. Thus it can be concluded that there is an effect of using hand puppet media on the listening skills of grade II students of SDN 6 Menteng Palangka Raya.